Kajian Filosofis Tradisi Magepokan Di Desa Sembiran Kecamatan Tejakula Kabupaten Buleleng - Kadek Suciani; Gede Mahardika; I Made Gami Sandi Untara (Vidya Darsan: Jurnal Mahasiswa Filsafat Hindu, 2022)
The magepokan tradition is one of the unique traditions in Sembiran Village, Tejakula District, Buleleng Regency. This magepokan tradition has been carried -out in the past by the community for generations. Every time the piodalan at Puseh Duur Temple in Sembiran Village on Purnama sasih kalima is believed to be symbolic so that all evil forces in Sembiran Village go away and do not destroy the plants and do not disturb the comfort of the community. People who live in Sembiran Village. From the background that has been described, this research will examine three problems, namely: 1) How is the basis of the magepokan tradition implemented in Sembiran Village, Tejakula District, Buleleng Regency?; 2) What is the function of implementing the magepokan tradition in Sembiran Village, Tejakula District, Buleleng Regency?; 3) What is the philosophical meaning of the magepokan tradition in Sembiran Village, Tejakula District, Buleleng Regency?. The theories used to dissect these problems are 1) Religious theory to dissect the first problem concerning the basis of the magepokan tradition carried out in Sembiran Village; 2) Structural Functional Theory to dissect the second problem regarding the function of the implementation of the magepokan tradition in Sembiran Village; 3) Hermeneutic theory to dissect the third problem regarding the meaning of philosophy contained in the magepokan tradition in Sembiran Village. The results obtained are 1) The foundation of the magepokan tradition carried out in Sembiran Village includes the historical basis, religious foundation and the procession of the implementation of the magepokan tradition from beginning to end; 2) The function of implementing the magepokan tradition in Sembiran Village includes: religious functions, ceremonial pamuput functions, functions of an embodiment of gratitude, and social functions and; 3) The philosophical meanings contained in the magepokan tradition in Sembiran Village include: the meaning of harmony, the meaning of togetherness, the meaning of repelling reinforcements, the meaning of ethics and the meaning of aesthetics.